2016
DOI: 10.1039/c5ta09464j
|View full text |Cite
|
Sign up to set email alerts
|

A highly stable CuS and CuS–Pt modified Cu2O/CuO heterostructure as an efficient photocathode for the hydrogen evolution reaction

Abstract: A Cu2O/CuO heterostructure modified with CuS is proposed as a highly promising and stable photocathode for solar hydrogen production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(101 citation statements)
references
References 42 publications
7
93
1
Order By: Relevance
“…The charge transfer resistance ( R ct ) significantly decreases from a value of 101 kΩ cm (CuO photocathode) to 28 kΩ cm after incorporation of G‐COOH into CuO film, as shown in Nyquist plot ( Figure ). The reduction in R ct value shows an increase in charge transfer activity for the CuO:G‐COOH composite film, which is due to the presence of electron acceptor group.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The charge transfer resistance ( R ct ) significantly decreases from a value of 101 kΩ cm (CuO photocathode) to 28 kΩ cm after incorporation of G‐COOH into CuO film, as shown in Nyquist plot ( Figure ). The reduction in R ct value shows an increase in charge transfer activity for the CuO:G‐COOH composite film, which is due to the presence of electron acceptor group.…”
Section: Resultsmentioning
confidence: 89%
“…Solar energy harvesting using photo‐electrochemical (PEC) water splitting is an emergent interest to convert solar energy into the fuel energy . The PEC water‐splitting technology requires semiconductor‐based photoelectrode to generate electron–hole pairs using solar light .…”
Section: Introductionmentioning
confidence: 99%
“…It was recently also used to deposit catalysts on semiconductor photoelectrodes to boost the PEC performance. For example, Hwang's group reported a Cu 2 O/CuO/CuS heterostructured photoelectrode, where CuS, as an electrocatalyst, was loaded on the Cu 2 O/CuO heterostructure via a SILAR approach . The authors used Cu(NO 3 ) 2 and Na 2 S as the source of Cu 2+ cations and S 2− anions, respectively, and found that only nine successive SILAR cycles could yield an optimal performance for light‐driven H 2 evolution ( Figure a).…”
Section: Strategies For Semiconductor/electrocatalyst Couplingmentioning
confidence: 99%
“…a) Fabrication of CuS on Cu 2 O/CuO photocathodes via a SILAR process . b) Chopped‐light J – V curve of Cu 2 O/CuO/CuS‐9‐Pt . c) J – V curves of Cu 2 O/CuO/CuS‐9‐Pt and the control samples.…”
Section: Strategies For Semiconductor/electrocatalyst Couplingmentioning
confidence: 99%
“…On the other hand, the presence of co‐catalyst (CuO or CoO) improves the photocatalytic activity of hydrogen production, due to formation of the p‐n heterojunction that effectively separates charge carriers. It is worth mentioning that CuO and CoO played different roles during the process: while CoO is expected to catalyze the O 2 evolution reaction, CuO is expected to catalyze the H 2 evolution reaction . However, the improvement by coupling ST with CuO is considerably greater than that obtained when the material is modified with CoO, indicating that reduction reaction is the controlling step in the photocatalytic process.…”
Section: Resultsmentioning
confidence: 99%